Evaluation of curcumin derivatives as new cyclooxygenase-2 inhibitors via in silico and in vitro analyses - Abdul Bahari, Mohammad Nazri (2016)
Prostaglandin E2 (PGE2) is one of the lipid mediators of inflammation. Chronic inflammation drives overproduction of PGE2 that leads to development of chronic inflammatory diseases. PGE2 is synthesized by cyclooxygenase (COX) enzyme that exists in isoforms of COX-1, which is constitutively expressed; and COX-2, which is expressed upon induction. Non-steroidal anti-inflammatory drugs (NSAIDs) inhibit COXs to control excessive production of PGE2 during inflammation but, most of commercialized NSAIDs selectively inhibit COX-1 or being non-selective which compensate for limitations and detrimental side effects of the medicine. Hence,deciphering the mechanisms of selectively inhibiting COX-2 is of great interest. Curcumin was known as remedy to treat the inflammatory-related diseases, but suffers from poor bioavailability and instability. Synthesis of curcumin derivatives was carried out to overcome the limitations. Thus, the objectives of this study are to investigate the effects of 43 curcumin derivatives towards activated cellular PGE2 production and COX’s activity, as well as to understand its mechanism of actions in silico and in vitro.In this study, effects of curcumin derivatives on PGE2 production in murine macrophage (RAW264.7) cells which was stimulated by combination of interferongamma (IFN-) and lipopolysaccharide (LPS), were evaluated using immunoassay procedures. Quantitative structure-activity relationship (QSAR) analysis was performed to correlate between the structure and PGE2 inhibition activity of curcumin derivatives.Enzymatic assay and molecular docking analysis were performed to decipher the mechanism of inhibition on COX activity by curcumin derivatives. Effects of active curcumin derivatives on gene expression of COX-1 and COX-2 were also determined.Results demonstrated that 3 out of 43 compounds significantly inhibited PGE2 production in IFN-γ/LPS-stimulated RAW264.7 cells dose-dependently which were 2,6-bis(2-fluorobenzylidene)cyclohexanone (compound 25), 2,6-bis(4-fluorobenzylidene)cyclohexanone (compound 27), and 2,5-bis(3,4,5-trimethoxybenzylidene)cyclopentanone (compound 43) with IC50 values of 6.15 ± 0.48 M, 5.78 ± 1.67 M and 12.15 ± 1.88 M respectively which were higher than that of curcumin. Furthermore, these three compounds were not toxic to the cells (cytotoxicity IC50>500 μM). The PGE2 inhibitory effect was contributed by the suppression of the IFN-γ/LPS-stimulated COX-2 gene expression, without affecting the phorbol myristate acetate (PMA)-stimulated COX-1 gene expression in RAW264.7 cells by these three compounds. Arene substitution patterns and substituents of electron withdrawing groups may contribute to the PGE2 inhibition activity of the compounds. Besides,QSAR study recommended that positive contribution of lipophilicity and numbers of rotatable bonds, and negative contribution of kappa_2 descriptor of the compounds were crucial for their anti-inflammatory properties. The enzymatic assay showed that most curcumin derivatives tested selectively inhibited COX-1 activity rather than COX-2. However, compounds 25 and 43 selectively inhibited COX-2, unlike compound 27 which favours towards COX-1 activity. Moreover, docking study revealed that compounds 25 and 43 interacted with COX’s active site receptors that favour towards COX-2 inhibition. Arg120, His90, Phe518 and Arg513 are important receptors involved in COX-2 inhibition, while Arg120 and Ser530 are important receptors in COX-1 inhibition. In conclusion, the experimental data have provided mechanistic insights into properties of compounds 25, 27, and 43 as COX-itors.Compounds 25 and 43 could be potential lead compounds for development of new COX-2 selective inhibitors.